2017
DOI: 10.1007/s00330-017-4790-3
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal subcortical nuclei shapes in patients with type 2 diabetes mellitus

Abstract: • Type 2 diabetes mellitus is accompanied with brain atrophy and cognitive dysfunction • Deep grey matter structures are essential for multiple cognitive processes • Shape analysis revealed local atrophy in the dorso-medial thalamus and caudatum in patients • Dorso-medial thalamic atrophy correlated to cognitive processing speed slowing and high HbA1c. • Shape analysis has advantages in unraveling neural substrates of diabetic cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Accordingly, processing speed reflects ability in the interaction of cognitive processes which are essential for higher order cognitive and mental function. Actually, localized atrophy of the thalamus was related to slower cognitive processing speeds in patients with multiple sclerosis (Bergsland et al., 2016; Bisecco et al., 2018) and Type 2 diabetes mellitus (Chen et al., 2017). Thus, the interaction of the thalamus and other regions play an important role in processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, processing speed reflects ability in the interaction of cognitive processes which are essential for higher order cognitive and mental function. Actually, localized atrophy of the thalamus was related to slower cognitive processing speeds in patients with multiple sclerosis (Bergsland et al., 2016; Bisecco et al., 2018) and Type 2 diabetes mellitus (Chen et al., 2017). Thus, the interaction of the thalamus and other regions play an important role in processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms have mainly been investigated in hippocampal neurons [ 18 , 19 , 20 , 21 , 22 , 23 ]. In addition, recent advances in neuroimaging, such as diffusion tensor imaging, have revealed that structural changes include not only areas associated with cognitive function, but also the motor and sensory cortices, basal ganglia, cerebellum, brainstem, and spinal cord, which are essential in generating and transmitting motor commands [ 24 , 25 , 26 , 27 ]. Furthermore, more direct data reveal changes in motor representations in the motor cortex and impaired conduction of the corticospinal tract (CST) in rodents with type 1 diabetes induced by streptozotocin (STZ) administration [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the caudate is involved in spatial working memory (49). Previous neuroimaging studies demonstrated that patients with T2DM exhibited lower gray matter volume in the caudate nucleus (5052). Prior studies showed that dysfunction of the caudate might lead to movement disorders, such as Parkinson’s disease and Huntington’s disease (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the caudate is involved in spatial working memory (49). Previous neuroimaging studies demonstrated that patients with T2DM exhibited lower gray matter volume in the caudate nucleus (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%